Biochemical characterization and technofunctional properties of bioprocessed wheat bran protein isolates. (15th August 2019) - Arte, Elisa; Huang, Xin; Nordlund, Emilia; Katina, Kati
Highlights: Lactic acid fermentation and hydrolytic enzymes were used for wheat bran bioprocessing. The protein content of the bran protein isolates was increased by bioprocessing. Bioprocessing altered the biochemical properties of the bran protein isolates. All bioprocesses improved the foaming stability of the bran protein isolates. Abstract: The effect of three combinations of bioprocessing methods by lactic acid fermentation, cell wall hydrolyzing enzymes and phytase on the biochemical (protein, fat, carbohydrate composition) and technofunctional properties (protein solubility, emulsifying and foaming properties) of wheat bran protein isolates were evaluated. The bioprocessing increased the protein (up to 80%) and fat content (up to 22.8%) in the isolates due to the degradation of starch and soluble pentosans. Additional proteins, globulin 3A and 3C, chitinase, β-amylase and LMW glutenins, were identified from the electrophoretic pattern of the protein isolate bioprocessed with added enzymes. Generally, the bioprocessed protein isolate had lower protein solubility and stronger net charge in pH below 7, when compared to the protein isolate made without bioprocessing. The emulsifying properties of the protein isolates were not affected by bioprocessing. However, the foaming stability of the protein isolates was nearly doubled by bioprocessing with cell wall hydrolyzing enzymes and phytase.